Analisa Biaya Kerugian Kemacetan Jalan Akibat Pelaksanaan Perbaikan Lapisan Base Course Menggunakan Cement Treated Base (CTB) (Studi Kasus : Ruas Jalan Laden – Bunder Kabupaten Pamekasan) - Ahmad Faqihul Muqoddam; Hera Widyastuti (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Road repair can be done by maintenance, Rehabilitation and Road Reconstruction. Road reconstruction can be done by replacing the base course layer. One of the materials to choose from is cement treated base (CTB). The implementation of road reconstruction resulted in traffic jams. Congestion occurs due to decreased road performance resulting in long queues, delays and additional vehicle operational costs. This will cause harm to road users. The method for calculating road user losses due to congestion during road repairs uses the Tzedakis method. The results of calculating the cost of losses during road repairs on the base course layer with a CTB thickness of 15 cm, a handling width of 3 meters and a handling length of 1000 meters are Rp. 2,905,814,453, -. Meanwhile, with a CTB thickness of 30 cm and a processing time of 24 days, the road congestion loss is Rp. 3,486,977,344, -